DEVELOPMENT OF A WEB-BASED ARCHIVE APPLICATION IN THE ADMIN AND SECRETARY DIVISION OF PT XYZ’S HEAD OFFICE - Anisa Salsabila; Ma’Mun Sutisna; Tangguh Dwi Pramono (Ebiz Prima Nusa, 2023)
An electronic filing system is something that is needed by companies as a record keeping of their archives. The condition of archives management in the Admin and Secretariat division of PT XYZ itself is currently not optimal, meanwhile archives are urgently needed to ensure the continuity of operational activities. Archive documents that have not been optimally arranged in filing cabinets make it difficult to retrieve archives and take around 10 to 15 minutes if at any time the archives are needed. This project aims to make an update from manual archives to website-based electronic archives which are solutions and innovations aimed at making 3the filing system more effective and efficient. With the waterfall method this application will assist in the process of managing records and provide information on archive category reports in the Admin and Secretarial Division and make it easier to find archives again. After testing, it was discovered that the website-based electronic filing application that was implemented was in accordance with the needs of both the manager and the website user because it makes work easier and shortens the time to manage and obtain archival information. Keywords: Archives, Electronic Archives, Information Systems, Applications, Websites